2013
DOI: 10.1126/scitranslmed.3005127
|View full text |Cite
|
Sign up to set email alerts
|

Mutant HSP70 Reverses Autoimmune Depigmentation in Vitiligo

Abstract: Vitiligo is an autoimmune disease characterized by destruction of melanocytes, leaving 0.5% of the population with progressive depigmentation. Current treatments offer limited efficacy. We report that modified inducible heat shock protein 70 (HSP70i) prevents T cell–mediated depigmentation. HSP70i is the molecular link between stress and the resultant immune response. We previously showed that HSP70i induces an inflammatory dendritic cell (DC) phenotype and is necessary for depigmentation in vitiligo mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 47 publications
1
122
0
2
Order By: Relevance
“…These innate immune responses activate dendritic cells, which carry and present melanocyte-specific antigens to T cells [10*, 15]. In addition, cytokines secreted by innate immune cells likely act as the initial signal to help T cells locate stressed melanocytes [10*, 16, 17].…”
Section: Autoimmunity In Vitiligomentioning
confidence: 99%
“…These innate immune responses activate dendritic cells, which carry and present melanocyte-specific antigens to T cells [10*, 15]. In addition, cytokines secreted by innate immune cells likely act as the initial signal to help T cells locate stressed melanocytes [10*, 16, 17].…”
Section: Autoimmunity In Vitiligomentioning
confidence: 99%
“…Interestingly, mutant HSP70iQ435A has been shown to prevent and reverse the depigmentation in different mouse models prone to vitiligo. These findings indicate a vital role of HSP70 in precipitation of vitiligo and targeting HSP70i might be a promising approach towards the treatment of vitiligo [242][243][244].…”
Section: Cross Talk Between Oxidative Stress Er Stress and Immune Symentioning
confidence: 78%
“…Mosenson et al [242] reported that modified HSP70i prevents T cell-mediated depigmentation. In addition, they have also shown HSP70i induces an inflammatory DC phenotype in both vitiligo mouse models as well as in vitiligo patients, which is necessary for depigmentation [242,243]. Interestingly, mutant HSP70iQ435A has been shown to prevent and reverse the depigmentation in different mouse models prone to vitiligo.…”
Section: Cross Talk Between Oxidative Stress Er Stress and Immune Symentioning
confidence: 97%
“…NK, CD11b + CD11c + cells, and macrophages infiltrate vitiligo lesions (37,38,56,57). Transcriptome and flow analysis of human skin revealed an infiltration of NK cells in lesional and non-lesional skin (56) which, in light of the recent discovery of NK-mediated killing of stressed melanocytes (36), could allow for a larger role in pathogenesis than previously thought.…”
Section: The Roles Of Other Cell Types Involved Are Poorly Definedmentioning
confidence: 99%